Syntrophic Partners Enhance Growth and Respiratory Dehalogenation of Hexachlorobenzene by Dehalococcoides mccartyi Strain CBDB1 - Chau, Anh T. T.; Lee, Matthew; Adrian, Lorenz; Manefield, Michael J. (Frontiers in Microbiology, 2018)
This study investigated syntrophic interactions between chlorinated benzene respiring Dehalococcoides mccartyi strain CBDB1 and fermenting partners (Desulfovibrio vulgaris, Syntrophobacter fumaroxidans and Geobacter lovleyi) during hexachlorobenzene respiration. Dechlorination rates in syntrophic co-cultures were enhanced 2-3 fold compared to H2 fed CBDB1 pure cultures (0.23 ± 0.04 µmol Cl- day-1). Syntrophic partners were also able to supply cobalamins to CBDB1, albeit with 3-10 fold lower resultant dechlorination activity compared to cultures receiving exogenous cyanocobalamin. Strain CBDB1 pure cultures accumulated ~1 µmol of carbon monoxide per 87.5 µmol Cl- released during hexachlorobenzene respiration resulting in decreases in dechlorination activity. The syntrophic partners investigated were shown to consume carbon monoxide generated by CBDB1, thus relieving carbon monoxide autotoxicity. Accumulation of lesser chlorinated chlorobenzene congeners (1,3- and 1,4-dichlorobenzene and 1,3,5-trichlorobenzene) also inhibited dechlorination activity and their removal from the headspace through adsorption to granular activated carbon was shown to restore activity. Proteomic analysis revealed co-culturing strain CBDB1 with Geobacter lovleyi upregulated CBDB1 genes associated with reductive dehalogenases, hydrogenases, formate dehydrogenase and ribosomal proteins. These data provide insight into CBDB1 ecology and inform strategies for application of CBDB1 in ex situ hexachlorobenzene destruction technologies.